The Future of Human Rights: Challenges and Opportunities for the Study (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article "The Future of Human Rights: Current Issues in the Study of Challenges and Opportunities" provides an in-depth analysis of the main challenges that threaten human rights globally: rising authoritarianism, climate change, and new types of conflict. The article emphasizes the need to reconsider the impact of such threats on human rights and ways to protect them. In particular, it offers strategies aimed at strengthening international cooperation, integrating human rights in the development of technology and promoting civil society. The article calls for new opportunities for the human rights movement to confront the challenges of the 21st century.